Rainfall runoff simulation using slop adjusted Curve number in Kuantan river basin - Amir Aizat, Jamil (2015)
The Natural Resources Conservation Service Curve Number (NRCS-CN) method is widely used for predicting direct runoff from rainfall. It believed that NRCS-CN has developed in an agricultural land with slope less than 5%, therefore it do not consider the effect of slope in the hilly and mountainous watersheds. Some researchers have investigated the effect of terrain slope on CN estimation. But on research can be found for assessment of slope on modified CN value and it is always a problem to find suitable source of elevation data to create slope map. It is significant that this is the first report on adjustment of Cell-based CN to determine the slope adjustment for CN using Sharply-Williams integrated with ASTER-GDEM. The adjusted CN was then tested for 25 observation rainfall runoff data. New slope adjusted CN demonstrate significant improvement from 0.12 to 0.39 in runoff estimation. This methodology can be carried out in different climate condition to get more inside CN for runoff estimation.